On the behavior of several fitness functions for genetically optimized microstrip antennas - Jayasinghe, Jeevani; Anguera, Jaume; Uduwawala, Disala (International Journal of Scientific World, 2015)
Genetic algorithm (GA) is a popular optimization technique used in the design of performance improved microstrip patch antennas (MPAs). The fitness function plays a vital role in the successful application of GA in MPAs.Â This paper investigates the performance of several fitness functions for achieving bandwidth improved MPAs.